2000
DOI: 10.1111/1467-8691.00198
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Understanding of Technology Management through Challenge Mapping

Abstract: The authors seek to clarify what is understood by the management of technology by involving a group of managers in a workshop to identify specifically what they believe to be their critical difficulties and challenges in managing technology. The approach is shown to be a means of enhancing creativity, designed not so much for creating good answers and solutions, but rather for discovering good questions and challenges and for conceptualizing complex issues. Virtually all of the challenges selected as most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…There is an opportunity for organizational leaders to model and use the four-stage process as a blueprint for getting the organization to cycle through of all four stages as a consistent organization-wide business innovation process just as they have standardized other business processes. One of the most discussed impediments to innovation in organizations is the so-called “silo effect.” Currently, most organizations lack the ability to move projects horizontally across the different departments from beginning to implementation (Basadur, Potworowski, Pollice, & Fedorwicz, 2001), partly because they lack a process for doing so. Perhaps organizational members can learn and build skills in synchronizing the different preferences for the stages of the process of various departments and influence members from different parts of the organization to work more efficiently and collaboratively through the process from generation to successful implementation of valuable changes.…”
Section: Implications For Managing Innovation and Changementioning
confidence: 99%
“…There is an opportunity for organizational leaders to model and use the four-stage process as a blueprint for getting the organization to cycle through of all four stages as a consistent organization-wide business innovation process just as they have standardized other business processes. One of the most discussed impediments to innovation in organizations is the so-called “silo effect.” Currently, most organizations lack the ability to move projects horizontally across the different departments from beginning to implementation (Basadur, Potworowski, Pollice, & Fedorwicz, 2001), partly because they lack a process for doing so. Perhaps organizational members can learn and build skills in synchronizing the different preferences for the stages of the process of various departments and influence members from different parts of the organization to work more efficiently and collaboratively through the process from generation to successful implementation of valuable changes.…”
Section: Implications For Managing Innovation and Changementioning
confidence: 99%
“…In another study, the Simplex system was applied to technology management (Basadur, Potworoski, Pollice, & Fedorowicz, 2000). The authors argue that techniques for group creativity (such as those found in Simplex) can play a significant role, addressing the new challenges of distributed teams, and project uncertainties.…”
Section: Creative Problem-solvingmentioning
confidence: 99%
“…Personenvironment fit (contingency) theories seem relevant also. Innovation leadership and entrepreneurship Manimala, (1992); Bessant (1992);de Cock (1993);Boyander & Miyake (1994;; Augsdorfer, (1994); Abetti (1995Abetti ( , 1997Abetti ( , 2000; Basadur, Potworoski, Pollice, & Fedorowicz, (2000) Roles in technological innovation generally assumed to operate within a rational model of strategic change (Tidd, Bessant, & Pavitt, 2001). Schumpeter (1934) offers an alternative and more radical model.…”
Section: Empowerment and Distributed Leadershipmentioning
confidence: 99%
“…Entrepreneurs have been shown to use framing to manage the perceptions of various stakeholders to gain legitimacy (Hargadon & Douglas, 2001; Rao, 1998). 2 Basadur and colleagues (e.g., Basadur, Ellspermann, & Evans, 1994; Basadur, Potworowski, Pollice, & Fedorowicz, 2000) demonstrated that framing questions by using specific words helped people be more proficient in formulating ill-structured problems. Their “why-what’s stopping” analysis combines analytical precision with structured imagination to help participants defer judgment and actively engage in divergent and convergent thinking, leading to a better definition of the problem to be solved (i.e., a reframed problem formulation).…”
Section: Literaturementioning
confidence: 99%